Designing fluorescent estrogen mimetic 7-hydroxycoumarin probe substrates for human sulfotransferase enzymes - Juvonen, Risto O.; Postila, Pekka A.; Singh, Pankaj Kumar; Huuskonen, Juhani; Timonen, Juri; Fashe, Muluneh; Hussain, Rasikh; Aqip, Zaeema; Kärkkäinen, Olli; Raunio, Hannu; Pentikäinen, Olli T. (Elsevier BV, 2026)
Sulfonation is one of drug metabolism reactions affecting homeostasis of estrogens. C-3 aryl substituted 7-hydroxycoumarins are fluorescent estrogen mimetics; i.e., the hydroxyl groups of both estrogens and 7-hydroxycoumarins are conjugated by human sulfotransferases (SULTs). Sulfonation of the 7‑hydroxyl group by SULTs decreases the fluorescence of 7-hydroxycoumarins. Sulfonation of a series of 7-hydroxycoumarins by human SULTs was determined based on this property. SULT subtype-specific binding interactions of 7-hydrocoumarins were assessed against the modelled optimal arrangement needed for sulfonation. 3-(4-Methoxyphenyl)-7-hydroxycoumarin (11) and 3-(4-hydroxyphenyl)-7-hydroxycoumarin (9) were selective substrates for SULT1E1, whereas 3-(1H-1,2,4-triazol-1-yl)-7-hydroxycoumarin (14) was a selective SULT1A1 substrate. Other tested 7-hydroxycoumarin were sulfonated by more than two SULTs. Sulfonation of most 7-hydroxycoumarins by SULT1A1 or SULT1C4 followed Michaelis-Menten kinetics, while substrate inhibition kinetics occurred in sulfonation of several derivatives by SULT1E1. Selective sulfonation of derivatives 9 and 11 by SULT1E1 was due to the enzyme's long and cylindrical active site that assures optimal 7‑hydroxyl group placement in the precursory reaction state. SULT1A1 and SULT1C4 preferred smaller derivatives as substrates than the SULT1E. Estrogens potently inhibited the sulfonation of 3,4-dimethyl-7-hydroxycoumarin (4) by SULT1E1 (IC50 below 1 µM). SULT1A1 and SULT1C4 were less potently inhibited by the estrogens. Several 7-hydroxycoumarin derivatives share common binding interaction patterns with the estrogens at SULT1E1 and SULT1A1 active sites. Fluorescent 7-hydroxycoumarins could serve as convenient probe substrates for SULTs to evaluate their inhibition by new chemical entities during drug development. 7-Hydroxycoumarins 9 or 11 could be used as selective probe substrates for SULT1E1 and 14 for SULT1A1.